Shipwrecked Disaster and Transformation in Homer, Shakespeare, Defoe, and the Modern World - Morrison, James V. (University of Michigan Press, 2016)
This book presents the first comparative study of notable literary shipwrecks from the past four thousand years, focusing on Homer's Odyssey, Shakespeare's The Tempest, and Defoe's Robinson Crusoe. James V. Morrison considers the historical context as well as the "triggers" (such as the 1609 Bermuda shipwreck) that inspired some of these works, and modern responses such as novels (Golding's Lord of the Flies, Coetzee's Foe, and Gordon's First on Mars, a science fiction version of the Crusoe story), movies, television (Forbidden Planet, Cast Away, and Lost), and the poetry and plays of Caribbean poets Derek Walcott and Aimé Césaire. For survivors who are stranded on an island for some period of time, shipwrecks often present the possibility of a change in political and social status-as well as romance and even paradise. In each of the major shipwreck narratives examined, the poet or novelist links the castaways' arrival on a new shore with the possibility of a new sort of life.